Akuno, Emily Achieng'. Music Education in Africa: Concept, Process, and Practice - Carver, Mandy (International Library of African Music, 2019)
pages: 164-167
Keywords: Book reviews; Curriculum planning; Education; Decolonisation; Music Education; Decolonial Practice; Pedagogy; Curriculum; African Music